2022
DOI: 10.1007/s11010-022-04534-w
|View full text |Cite
|
Sign up to set email alerts
|

PUM2 aggravates the neuroinflammation and brain damage induced by ischemia–reperfusion through the SLC7A11-dependent inhibition of ferroptosis via suppressing the SIRT1

Abstract: Cerebral ischemia–reperfusion (I/R) injury occurs due to the restoration of blood perfusion after cerebral ischemia, which results in the damage of the brain structures and functions. Unfortunately, currently there are no effective methods for preventing and treating it. The pumilio 2 (PUM2) is a type of RBPs that has been reported to participate in the progression of several diseases. Ferroptosis is reported to be involved in I/R injury. Whether PUM2 modulated I/R injury through regulating ferroptosis remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Numerous studies have proposed the functions of Sirt1 in ferroptosis. Liu et al found that pumilio 2 (PUM2) aggravated the neuroinflammation and brain damage induced by ischemia–reperfusion through ferroptosis by inhibiting the Sirt1 [ 133 ]. Moreover, Li et al [ 134 ] proposed that Sirt1 upregulation attenuated ferroptosis levels in ischemic ischemic hypoxic–ischemic brain injury and improved learning and memory via the Nrf2/GPx4 signaling pathway.…”
Section: The Therapeutic Role Of Sirt1 In Sahsmentioning
confidence: 99%
“…Numerous studies have proposed the functions of Sirt1 in ferroptosis. Liu et al found that pumilio 2 (PUM2) aggravated the neuroinflammation and brain damage induced by ischemia–reperfusion through ferroptosis by inhibiting the Sirt1 [ 133 ]. Moreover, Li et al [ 134 ] proposed that Sirt1 upregulation attenuated ferroptosis levels in ischemic ischemic hypoxic–ischemic brain injury and improved learning and memory via the Nrf2/GPx4 signaling pathway.…”
Section: The Therapeutic Role Of Sirt1 In Sahsmentioning
confidence: 99%
“… Liang et al (2023) showed that mitochondrial damage resulting from SIRT1 inactivation played an important role in ferroptosis caused by Epothilone B in schwann cells. Liu et al found identified that pumilio 2 (PUM2) promoted ferroptosis by inhibiting SIRT1/SLC7A11, aggravated neuroinflammation and brain damage induced by ischemia-reperfusion injury ( Liu et al, 2023 ). In addition, activation of SIRT1 and GPX4 by calorie restriction protects against the ferroptosis-caused kidney injury in the Sprague Dawley rat model of contrast-induced nephropathy ( Fang et al, 2021 ).…”
Section: Roles Of Sirtuins In Ferroptosismentioning
confidence: 99%
“…Ferritin also significantly reduces tau hyperphosphorylation and oxidative stress [ 113 ]. Accordingly, the role of the Tau protein is age-dependent in cerebral IRI [ 114 ], and Tau can promote iron transfer in aging-related ischemic stroke to mitigate ferroptosis [ 115 ]. Additionally, NCOA4 mediates the excessive degradation of ferritin caused by ferritinophagy during cerebral I/R followed by ferroptosis [ 116 ].…”
Section: Mechanisms and Targeted Therapies For Ferroptosis In Irimentioning
confidence: 99%
“…SLC7A11 mediates the synthesis of glutathione, which is available to GPX4 to reduce lipid peroxidation. However, PUM2 attenuates the inhibitory effect of SLC7A11 on ferroptosis by suppressing SIRT1 expression, thus exacerbating I/R-induced neuroinflammation and brain injury [ 114 ]. In tert-butyl-hydroxyperoxide-treated neurons, activation of the SSAT1/ALOX15 axis downregulated the expression of GPX4 and SLC7A11, which triggered neuronal death and worsened IRI [ 118 ].…”
Section: Mechanisms and Targeted Therapies For Ferroptosis In Irimentioning
confidence: 99%